Application of the guadua for the construction of roofs with earth, based on the “domocaña” (2019)
This article describes the experimental work of construction of several houses made with the guadua and land cover technique called “domocaña”, innovation carried out at the National Engineering University of Peru. This is a recent transfer, it only takes about a decade of application in Colombia; There are several experimental and demonstrative works that were built with this technique, by professionals who accept the challenge of innovation for knowledge development. This technical proposal is considered to be valid and merits deeper work, since the roofs that have been built are versatile, ecological, durable, beautiful, climate and acoustically comfortable, economical and simple to develop alternatives. This paper proposes to stimulate the study of this technique from the description of the experiences to transfer what has been learned from the constructive practice, with the successes and difficulties. All this by virtue of which for low-cost housing covers is an alternative that has a high potential; hence the intention is to motivate other professionals and researchers, including study centers such as universities, to deepen scientifically in this construction proposal.